BABIES MOTOR DEVELOPMENT INSERTED IN DIFFERENT STIMULATION PROGRAMS. (Fiep Bulletin - online, 2013)
Despite the limited act of physical education professional with babies interventions in schools or in daycare, recent studies have appointed to an urgent review motor stimulation programs in this stage of life and tools that can infer the quality of motor behavior are essential for babies analyzes of the unfolding of interventionist initiatives. This study aimed to analyze babies motor development inserted in different stimulation programs. We analyzed 15 babies of both gender, mean age 9.5 ± 2.1 months of two nurseries, one municipal and other private. The group analysis showed that 25% of babies in daycare are classified with risk for motor delays while others present favorable motor development. For private school 9% of babies had full motor development while, 19% had motor development and 73% favorable signals risk for motor delays. In conclusion it was shown that 7% of the total sample have levels of full motor development, motor development have 33% and 60% favorable signals of risks to motor delay.
Keywords: Babies; stimulation programs; AIMS